A Multicarrier PWM Technique for Five Level Inverter Connected to the Grid - M. Khanfara; R. El Bachtiri; M. Boussetta; K. El Hammoumi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In this paper, a three-phase multilevel cascaded H-bridge inverter is developed for injecting renewable power energy into the grid through a filter. The main contribution of this work is to reduce the total harmonic distortion (THD) by using a passive filter and to enhance the output voltages by adopting a multicarrier pulse width modulation (MCPWM). The simulation results affirm a good performance of the proposed multicarrier PWM control using a three-phase five-level inverter. The proposed inverter is tested as well as the THD and the spectral analysis of the output voltage are calculated using Simulink/Matlab software.